2019
DOI: 10.1155/2019/8202160
|View full text |Cite
|
Sign up to set email alerts
|

Development of UV Spectrophotometric Procedures for Determination of Amlodipine and Celecoxib in Formulation: Use of Scaling Factor to Improve the Sensitivity

Abstract: FDA has recently approved a new fixed-dose combination of amlodipine besylate (AMD) and celecoxib (COX) for the treatment of hypertension and osteoarthritis. No analytical method has been reported for analysis of these two analytes so far. Hence, to monitor the quality and quantity in the formulation of AMD and COX a simple, accurate, precise, economical, and eco-friendly spectroscopic analytical method has been established. The first method involves the determination of AMD and COX by the first derivative UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…However, the straight UV absorption technique for the simultaneous quantification of both analytes is challenging without prior separation. Such binary mixtures can be quantified by eliminating interference from one another using possible modification procedures such as derivative, ratio spectroscopic, and ratio subtraction methods [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. To increase the sensitivity of the low concentration, the BEN scaling factor was optimized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the straight UV absorption technique for the simultaneous quantification of both analytes is challenging without prior separation. Such binary mixtures can be quantified by eliminating interference from one another using possible modification procedures such as derivative, ratio spectroscopic, and ratio subtraction methods [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. To increase the sensitivity of the low concentration, the BEN scaling factor was optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Derivative spectroscopic methods allow quantification of compounds having complete overlapping spectra by computing the peak height at the zero-crossing point. The ratio derivative spectroscopic method removes the effect of one of the components by dividing the combined spectra of analytes with the spectrum of another component [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Hence, derivative and ratio derivative spectrophotometric methods were developed in the present work.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have reported different analytical methods for the quantification of the above fixed dose combination in synthetic mixtures, pharmaceutical formulation and biological fluids. For instance, UV [8][9][10][11][12] , TLC 13 , HPLC [14][15][16] and LC-MS/MS 17 methods have been developed. Overall, 10 studies have been reported for the estimation of Celecoxib and Amlodipine simultaneously among which only two papers had described quantification of the two drugs in biological samples using HPLC and LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…Telmisartan, olmesartan, and irbesartan are available on the market in combination with amlodipine and hydrochlorothiazide (Figure 1), manufactured by the same or different pharmaceutical industries [4]. Different analytical methods such as spectrophotometric [11][12][13][14][15][16][17][18], derivative spectrofluorimetric [19], HPLC [20][21][22][23][24][25][26][27], electrophoresis [28], and HPTLC [29] were reported for the concurrent determination of sartans, amlodipine, or hydrochlorothiazide from formulations and biological fluids. The literature has also reported a few analytical methods for the concurrent determination of ternary mixtures of sartans, amlodipine, and hydrochlorothiazide [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%